(untitled) - Houston, Mark C (Philadelphia, 2000)
Hypertension is one of the major rish factors for coronary heart disease (CHD), cerebrovascular accident (CVA), chronic renal failure (CRF), and congestive heart (CHF) in the United States.
Keywords: Hypertension,Bệnh cao huyết áp,Hypertension,Bệnh cao huyết; Handbooks, manuals, etc.,Sổ hướng dẫn, sổ thông tin,etc,Drug therapy,Liệu pháp trị bệnh bằng thuốc